The Distribution and Population Density of Bornean Tarsier, "Tarsius Bancanus Borneanus (Elliot)" in Secondary and Rehabilitated Forests of Universiti Putra Malaysia, Bintulu Sarawak Campus, Sarawak, Malaysia - Hani Nabilia Muhd Sahimi; John Keen Chubo; Marina Mohd. Top @ Mohd. Tah; Noor Bahiah Saripuddin; Siti Sarah Ab Rahim (Tropical Life Sciences Research, 2018)
Tarsius bancanus borneanus was first reported by Elliot in 1990 which an endemic species that can be found on the Island of Borneo consisting of Sabah and Sarawak of Malaysia, Brunei Darussalam and Kalimantan, Indonesia. This sub-species has been listed as a totally protected animal under the Sarawak Wild Life Protection Ordinance (1998) and vulnerable by the International Union for Conservation of Nature (IUCN). The present study was conducted at Universiti Putra Malaysia Bintulu Campus (UPMKB), Sarawak from October 2014 till March 2015. Through mark and recapture sampling covering an area of 37 ha of secondary forest patches and 7.13 ha of rehabilitated forest, a total of 16 tarsiers were captured using mist nets while one tarsier was recapture. The population density was 38 individuals/km2 was captured using mist nets in the secondary forest while 28 individuals/km² was recorded for the rehabilitated forest. Using the catch per unit effort (net hour) method, the average time for capturing tarsiers in the secondary forest patches was 26.6 net hour per animal and 30.0 net hour per animal in the rehabilitated forest. The presented results provides information on the presence of tarsiers in both the secondaryand rehabilitated forests of UPMKB, Sarawak, Malaysia which underlines the conservation value of these forested areas. Tarsius bancanus borneanus (kera hantu) pertama kali dicam oleh Elliot pada tahun 1990 merupakan spesies endemik yang boleh ditemui di kepulauan Borneo yang terdiri dari Sabah dan Sarawak (Malaysia), Brunei Darussalam dan Kalimantan, Indonesia. Sub-spesies ini telah disenaraikan sebagai haiwan yang terlindung sepenuhnya di bawah Ordinan Perlindungan Hidupan Liar Sarawak (1998) dan disenaraikan sebagai spesies yang terdedah kepada kepupusan oleh IUCN. Kajian ini telah dijalankan di Universiti Putra Malaysia Kampus Bintulu Sarawak (UPMKB), dari Oktober 2014 hingga Mac 2015. Menerusi persampelan tangkap-lepas yang meliputi kawasan seluas 37 ha hutan sekunder dan 7.13 ha hutan yang dipulihara, sebanyak 16 ekor kera hantu telah ditangkap menggunakan jarring kabut manakala seekor kera hantu telah berjaya ditangkap semula. Kepadatan populasi kera hantu yang ditangkap menggunakan jaring kabut di dalam hutan sekunder adalah 38 individu/km2 manakala 28 individu/km2 dicatatkan bagi hutan yang dipulihara. Dengan menggunakan kaedah penangkapan per satu unit usaha (net-jam), masa purata bagi seekor kera hantu ditangkap di dalam hutan sekunder adalah 26.6 jam/haiwan dan 30 jam/haiwan di dalam hutan yang dipulihara. Keputusan membuktikan data mengenai kehadiran kera hantu di dalam kedua-dua hutan sekunder dan hutan yang dipulihara terutamanya di kampus UPMKB sekaligus menonjolkan nilai pemuliharaan kawasan hutan tersebut.